Le patriarcat ou le féminisme noir - Charlery, Hélène (Revue française d’études américaines, 2007)
Les travaux actuels parus sur le féminisme et la population noire aux États-Unis insistent fréquemment sur l’attitude des Africaines-Américaines à l’égard de l’idéologie féministe (Terrelonge ; Roth). Peu d’études en revanche ont été consacrées aux prises de position des hommes et des dirigeants noirs sur la question. D’après les analyses récentes, une majorité d’Africains-Américains, hommes et femmes, redouterait que le féminisme ne divise les genres au sein du groupe, qu’il n’écarte les Noirs de leur priorité dans la lutte contre la discrimination raciale ou encore qu’il n’engendre un débat médiatique sur la sexualité des Africains-Américains. À ces raisons, Pauline Terrelonge ajoute l’héritage du nationalisme noir de la seconde moitié des années 1960 (Terrelonge 563). On constate aussitôt que les prises de positions citées précédemment sont liées à l’histoire des Noirs aux États-Unis et de leur stigmatisation dans les discours dominants. Pour les Africains-Américains, le féminisme imposerait alors une confrontation entre la race et le genre, bien que les féministes noires aient toujours envisagé de prendre en compte « l’intersectionalité » des deux notions .
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; masculinité; patriarcat; pol5185; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; états-unis

The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions

Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Number: 1 Publisher: Persée - Portail des revues scientifiques en SHS
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Le témoin modeste: diffractions féministes dans l'étude des sciences dans Manifeste cyborg et autres essais - Haraway, Donna Jeanne (Manifeste cyborg et autres essais, 2007)
Cette anthologie propose les textes essentiels de Donna Haraway : Cyborg manifesto, Situated knowledge, Teddy bear patriarchy, Ecce homo, Modest witness, Race.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; patriarcat; point de vue situé; premier cycle; pédagogie; périodes historiques; régions géographiques; savoir situé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Queer Theory and Sociology: Locating the Subject and the Self in Sexuality Studies - Isaiah Green, Adam (Sociological Theory, 2007)
In this paper, I revisit the relationship of queer theory and sociology in order to address some critical issues around conceiving the subject and the self in sexualities research. I suggest that while sociology and queer theory are not reducible to each other, sociology has its own deconstructionist impulse built into pragmatist and symbolic interactionist analyses of identity and subjectivity that is often overlooked by or reinvented through queer theory. But, conversely, queer theory has a very specific deconstructionist raison d'etre with regard to conceiving the sexual subject that marks its key departure from Foucault and sociology more generally. This deconstructionist mandate, by definition, moves queer theory away from the analysis of self and subject position—including those accruing from race, class and gender—and toward a conception of the self radically disarticulated from the social. This “anti-identitarian” position has been a source of criticism among some sociologists who find in queer theory an indefensible “refusal to name a subject” ( Seidman 1993:132). But this criticism, I suggest, stems from a misplaced effort to synthesize queer theory and sociology when, in fact, the two approaches to the subject are founded on incommensurable methodological and epistemological principles. Rather, I argue that the very promise of queer theory rests in a strong deconstructionism that exists in tension with, rather than as an extension of, sociological approaches to the self
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; thématiques